2016
DOI: 10.3892/mmr.2016.5958
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of histone H3 lysine 9 dimethylation in peripheral white blood cells of septic patients with trauma and cancer

Abstract: The present study aimed to investigate the clinical significance of histone methylation in sepsis. A total of 43 blood samples from trauma and esophageal cancer patients with or without sepsis were collected. Immunofluorescence staining of isolated peripheral white blood cells (WBCs) was conducted. Co-stained 293T cells served as a reference, to allow the levels of histone methylation in different types of WBCs from patients to be determined. Immunostaining analyses revealed different levels of histone 3 lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…From an in vivo point of view, this approach paves the way for systematic deciphering of modulated retroviral elements associated with autoimmune diseases such as systemic lupus erythematosus, inflammatory diseases such as type 1 diabetes [ 79 ] inherited autoimmune and auto-inflammatory disorders such as type 1 interferonopathies (reviewed in [ 80 , 81 ]), and virus- or drug-induced immunocompromised states [ 82 ], as well as resulting from a compensatory response to hyperinflammation such as in sepsis [ 83 ]. Notably, it would be of interest to investigate whether the altered histone methylation recently observed for genes in LPS-induced tolerance and in septic patients [ 75 , 84 ] may affect HERV expression and contribute to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…From an in vivo point of view, this approach paves the way for systematic deciphering of modulated retroviral elements associated with autoimmune diseases such as systemic lupus erythematosus, inflammatory diseases such as type 1 diabetes [ 79 ] inherited autoimmune and auto-inflammatory disorders such as type 1 interferonopathies (reviewed in [ 80 , 81 ]), and virus- or drug-induced immunocompromised states [ 82 ], as well as resulting from a compensatory response to hyperinflammation such as in sepsis [ 83 ]. Notably, it would be of interest to investigate whether the altered histone methylation recently observed for genes in LPS-induced tolerance and in septic patients [ 75 , 84 ] may affect HERV expression and contribute to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The methy l-D 3 -SAMe enrichment in patients was higher at the initial time point and showed a rapid decline until 24 h followed by a steady state decay, which was lower than that of controls, indicating that SAMe may be prioritized to maintain methyl balance or used for other methyl-dependent pathways instead of PEMT-mediated hepatic PC synthesis. While no direct evidence is available that increased hepatic SAMe turnover contributes to the pathogenesis of ARDS, increased SAMe-dependent histone methylation is an important component of the inflammatory response in sepsis and cancer ( 30 ). Alternatively, enhanced SAMe turnover could have been partly due to decreased synthesis, and inhibition of liver SAMe synthetase has been reported in an endotoxic rat model of septic shock ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, curcumin inhibits TREM-1 by suppressing the methylation and acetylation of H3K4, and studies have suggested that curcumin is also able to inhibit tumor growth [181,200]. In addition, Jiang et al (2016) examined the clinical significance of histone methylation in esophageal cancer patients, and results show that increased levels of H3K9me2 are to be found in neutrophils when compared with samples acquired from trauma patients [201]. Another study examined the epigenetic alterations of the ALX/FPR 2 gene, which activation exerts anti-inflammatory effects, and its potential in breast cancer treatment [202].…”
Section: Histone Modification In Neutrophilsmentioning
confidence: 99%